Stress Management Skills of The Public Teachers and their Classroom Efficiency - Martel, Arniel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the stress management skills of public elementary school teachers and their relationship to classroom efficiency in the Danao City Division for the school year 2025–2026. Anchored on Social Cognitive Theory, the Transactional Model of Stress and Coping, and the Coping-Competence-Context Theory of Teacher Stress, the study used a descriptive-quantitative correlational design. Data were gathered from 246 public elementary school teachers selected from a population of 637 through stratified random sampling. An adapted survey questionnaire measured respondents’ background characteristics, perceived stress management skills, and perceived classroom efficiency. The data were analyzed using frequency, percentage, mean, weighted mean, standard deviation, and Pearson Product-Moment Correlation Coefficient. Findings showed that respondents generally had very high stress management skills, with social support and communication receiving the highest rating, while healthy lifestyle practices obtained the lowest but still high rating. Respondents also reported very high classroom efficiency, particularly in classroom management, student engagement and motivation, and professionalism and reflective practice. Correlation results revealed that all stress management components were significantly and positively related to classroom efficiency, with social support and communication, professional development, and coping strategies showing the strongest relationships. The study concluded that teachers with stronger stress management skills tend to demonstrate higher classroom efficiency. It recommended in-service stress management training, wellness activities, and adoption of the proposed Stress Reduction for Maximum Classroom Effectiveness and Enhancement Plan. The study supports SDG 3, SDG 4, SDG 8, and SDG 16 by promoting teacher well-being, quality education, decent work, and institution-based mental health support. Its sustainability impact lies in strengthening public health, educational, workplace, and institutional sustainability through healthier teachers and more effective classrooms.
Keywords: Classroom Efficiency; Coping Strategies; Professional Development; Stress Management Skills; Teacher Well-Being